Edukasi Keluarga Mahasiswa tentang Pencegahan dan Deteksi Dini Penyakit Kronis - Basri, Muhammad; Sibulo , Megawati; Kistan, Kistan; Irawati, Irawati; Najman, Najman (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2025)
Chronic diseases in Indonesia remain a serious challenge in improving the quality of life of the community, particularly in terms of prevention and early detection of chronic diseases. This community service activity aims to educate family members of students on preventing and detecting chronic diseases, particularly diabetes mellitus and stroke, by adopting a healthy lifestyle, maintaining a balanced diet, reducing excessive consumption of sugar, salt, and fat, and engaging in regular light physical activity daily. Additionally, participants are encouraged to regularly monitor blood pressure and blood sugar levels, manage stress, and ensure adequate rest. The activity was conducted over two weeks through three stages: preparation, implementation, and evaluation. The community service activity was carried out in three stages: preparation, implementation, and evaluation. The results of this activity found that there was a 62% increase in knowledge about the prevention and detection of Diabetes Mellitus, a 57% increase in knowledge about the prevention and detection of stroke, and a 54% increase in knowledge about the role of nutrition, healthy lifestyle, and physical activity. Additionally, there was a 54% change in behaviour for the prevention and early detection of Diabetes Mellitus, a 35% change for the prevention and early detection of stroke, 32% for the role of nutrition, activities, and healthy lifestyles among student families affected by Diabetes Mellitus and stroke. This was measured by assessing blood sugar levels and blood pressure before and after the activity, which showed a decrease of 16% in blood pressure and 11% in blood sugar levels. It is hoped that after this activity, participants can apply the knowledge gained in their daily lives and serve as role models for children in fostering a culture of healthy living. Translated with DeepL.com (free version).